2023
DOI: 10.2147/jmdh.s421060
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Scale Measuring the Post Pandemic-Health Promotion Behavior (PP-HPB) of Young Adults in the Digital Era

Myoung-Lyun Heo,
Yang-Min Jang,
Hyun-Young Kim

Abstract: This study aims to develop and validate a health promotion behavior scale that reflects the lifestyle changes driven by the COVID-19 pandemic and the increased use of digital devices among young adults. Methods: Questions were selected using a literature review and validated by a group of experts. The sample consisted of 446 young adults aged 19-29 years living in South Korea who agreed to participate in the study and were surveyed online using Google Forms on September 19 and 20, 2022. Construct validity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…While the current study found a strong correlation between HPB and QoL, one notable difference from previous studies is that we analyzed PP-HPB scores, which were developed specifically for young adults, and incorporated questions related to health behaviors using mobile devices. The analysis indicated that dietary habits and physical activity levels were the lowest of all the categories, consistent with findings from similar studies [26,36]. These similar results across multiple studies highlight the challenges to basic health behaviors such as diet and physical activity due to the prevalence of online-centric lifestyles and convenience foods [36], suggesting that improvements in these areas could potentially influence the relationship between anxiety and QoL.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…While the current study found a strong correlation between HPB and QoL, one notable difference from previous studies is that we analyzed PP-HPB scores, which were developed specifically for young adults, and incorporated questions related to health behaviors using mobile devices. The analysis indicated that dietary habits and physical activity levels were the lowest of all the categories, consistent with findings from similar studies [26,36]. These similar results across multiple studies highlight the challenges to basic health behaviors such as diet and physical activity due to the prevalence of online-centric lifestyles and convenience foods [36], suggesting that improvements in these areas could potentially influence the relationship between anxiety and QoL.…”
Section: Discussionsupporting
confidence: 81%
“…Thus, encouraging such behaviors among anxious young adults is a pivotal strategy for enhancing QoL. Particularly, the PP-HPB instrument used in this study reflects the online-centric lifestyle and health perceptions of the younger generation [26], providing a rationale for actively offering HPB intervention programs to young adults in today's rapid-paced society.In other words, while anxiety and QoL are typically addressed as psychological variables, based on the findings of this study, managing anxiety and QoL in young adults requires not only psychological approaches but also strengthening health promotion strategies that encompass various factors such as dietary habits, physical activity, and more.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation